Перенапруги в анормальних режимах ліній електропередачі надвисокої напруги - Кузнецов, В.Г.; Тугай, Ю.І.; Кучанський, В.В. (Технічна електродинаміка, 2012)
The reason of overvoltage at the abnormal conditions in transmission lines of UHV are researched. The source of parameters distortion which causes specific overvoltage under at the open-phase operating conditions of transmission lines is given. Formulas which allow to find components of compensation shunt reactor of ground capacitance and interphase capacitance of transmission line are obtained. The mathematical model which simulates the physical processes in UHV overhead transmission lines at the open-phase condition are resulted. The next research must show the influence of longitudinal unsymmetry on the parameters of overvoltage.